A Systematic Literature Review: The Relationship Between Indonesian Culture and Other Aspects - Mubarok, Husni; Fadilah, Nurul; Toyyib, Moh (Journal Intellectual Sufism Research (JISR), 2021)
This article aimed to present the relationship between Indonesian culture with various aspects (education, welfare, arts, and religion) and showing the uniqueness of Indonesian culture. The procedural of this systematic review used the Suprapto et al., (2020) guided method, including defining the purpose, conducting literature, selecting articles, reading full paper, abstracting data, and performing analysis. The articles' criteria to be analyzed must be in the English version, published in the social sciences citation indexed (SSCI) journal in the period of 2016-2020. The articles included four fields (education, welfare, art, and religion) as a representation of Indonesian intercultural in several aspects. The result of this study showed that there was an interplay between Indonesian culture and four aspects of the fields, even between aspects. Although Indonesia has a lot of cultures and several aspects would be influenced, however, religion is the strongest aspect related to Indonesian culture.